Outcomes of peripherally inserted central catheter vs conventional central venous catheters in hematological cancer patients: a systematic review and meta-analysis - Weilei Ge; Chen Zheng (Hematology)
Objective This review aimed to examine if there is any difference in the risk of thrombosis and central line-associated bloodstream infection (CLABSI) with the use of peripherally inserted central catheter (PICC) and conventional central venous catheters (CVC) in hematological cancer patients.Methods We searched the online databases of PubMed, CENTRAL, Scopus, Web of Science, and Embase for all types of studies comparing the risk of thrombosis and CLABSI between PICC and CVC. The search ended on 23rd September 2024.Results Eight studies were included. One was a randomized trial while others were observational studies. Meta-analysis showed no statistically significant difference in the risk of thrombosis between PICC and CVC (OR: 1.69 95% CI: 0.75, 3.82 I2 = 78%). However, these results were not stable on sensitivity analysis. The exclusion of two studies indicated a higher risk of thrombosis with PICC. Pooled analysis showed that the risk of CLABSI was significantly lower with PICC as compared to CVC (OR: 0.52 95% CI: 0.40, 0.66 I2 = 0%). Results of subgroup analysis based on study design and diagnosis showed conflicting results.Conclusions There is conflicting evidence on the risk of thrombosis between PICC and CVC when used for hematological cancer patients. There could be a tendency of higher risk of thrombosis with PICC which needs to be confirmed by further studies. However, the use of PICC may reduce the risk of CLABSI in such patients. The quality of evidence is low owing to the predominance of observational studies with high inter-study heterogeneity.